Politics of participation in sustainable development governance/ edited by Jessica F. Green and W. Bradnee Chambers - "Green,Jessica F. (ed.)" (New Delhi, 2006)
To be effective and legitimate, the governance of sustainable development requires the participation of a diverse set of actors ranging from transnational civil society groups to indigenous peoples. This book explores the extent to which the current system of governance allows for the participation of diverse actors and finds that there are still many obstacles impeding the inclusion and influence of a number of different groups. The authors examine the obstacles to effective participation and how they can be overcome to improve both the quality of engagement and the resulting systems of sustainable development governance. They offer a working definition of engagement, and describe formal and informal methods for participating in and influencing global policymaking. They examine a number of current policymaking processes, draw lessons from successful examples, and provide recommendations for future improvements in the governance of sustainable development. This book is a useful resource for academics and policymakers, as well as groups seeking greater input into sustainable development governance.
Keywords: Politics and participation